Ethnicity and Relation with the Other in Immigrant Intensive Metropolitan Cities - Duman, Betul (ISTANBUL UNIV, FAC LETTERS, DEPT SOCIOLOGY, 2013)
Resting on the assumption that confrontations do matter among different ethnic groups, this article asks the question of which encounters stimulate ethnic conscious/conflict and which of them produce solidarities that discourage and substitute ethnic identities in metropolitan cities which attracted great deal of ethnic migration. It is found that the presence or absence of economic competition among ethnic groups and the quality of that competition can produce ethnic competition/conflict which can further articulate into political competition when it combines with the power-threat perception. In this article, findings of a project supported by TUBITAK under the name of Kurdish Issue in the Context of Social Cohesion (110K474) have partially been used. 451 field surveys belonging to Adana, Mersin and Antalya region and 39 deep interviews carried out in Mersin have been analyzed.
Keywords: Ethnic Competition; Power-Threat Perception; Political Polarization; Intergroup Contact; Kurdish and Turkish Ethnic Identity; Sociology